2011
DOI: 10.5455/vetworld.2011.82-83
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative potential of Psidium guajava in induced arsenic toxicity in Wistar rats

Abstract: The study was undertaken to determine the effect of Psidium.guajava leaf extract on arsenic induced biochemical alterations in Wistar rats. Significant (P<0.05) increased glucose serum urea nitrogen and serum creatinine was observed whereas non significant decrease in total protein, calcium and phosphorus was observed. It is concluded that kidney damage caused by arsenic can be repaired up to some extent by AEPG 50.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Consistent with the studies reported in this study, it was determined that the rats in the arsenic-treated group had the highest K (p˂0.05) and Na (numerically, p>0.05) levels and that sodium arsenite could cause imbalances in electrolyte levels due to impaired kidney function. Roy and Roy (2011) found that serum phos- : Different letters in the same row mark statistical difference between values. (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the studies reported in this study, it was determined that the rats in the arsenic-treated group had the highest K (p˂0.05) and Na (numerically, p>0.05) levels and that sodium arsenite could cause imbalances in electrolyte levels due to impaired kidney function. Roy and Roy (2011) found that serum phos- : Different letters in the same row mark statistical difference between values. (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Maintains the cellular integrity of testicular cells and improves sperm quality parameters in rats [126] Ipomea aquatica Amelioration of antioxidant parameters in liver, kidney, heart, brain and testis in mice [127] Tamarindus indica Regulation of serum hepatic and oxidative stress markers in rats [128] Triticum aestivum…”
Section: Withania Somniferamentioning
confidence: 99%
“…A large number of researches confirmed the beneficial effect of Glycine max [122], Sesamum indicum [123], Satureja hortensis [124] Withania somnifera [125,126], Ipomea aquatica [127], Tamarindus indica [128], Royal jelly [129], and Terminalia chebula [130] on arsenic and cadmium toxicities reduction. Concerning the effects of natural products on arsenic toxicity in ruminants, it was reported that Curcuma longa, Zingiber officinale, and Amaranthus spinosus have eliminated the absorption of arsenic from the bovine body and protected against DNA fragmentation in these species [131,132].…”
Section: Arsenic and Cadmium Toxicity Preventionmentioning
confidence: 99%